Faktor – Faktor Penyebab Kejadian Infeksi Saluran Pernafasan Akut (Ispa) Di Musim Kemarau Pada Masyarakat Wilayah Kerja Puskesmas Kampar - Usman, Wahyuni; Taruna, John; Kusumawati, Nila (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
ARI (Acute Respiratory Infection) is an acute inflammation of upper and lower respiratory tract caused by infection of microorganisms or bacteria, viruses, or rickets, without or with inflammation of the lung parenchyma. ARI is caused by a virus / bacteria that begins with heat accompanied by one or more symptoms such as sore throat, swallowing pain, runny nose, dry cough or phlegm. ARI is a public health problem in developing countries. The incidence of ARI tends to increase during the dry season.The goal of this research is want to know factors causing the event of ARI in dry season at public health center of kampar 2020. This research is observational analytic study with case control study design. Based on the results of research in the Kampar Public health center. The population is suffering from this research is the people in the Kampar Public health center and the samples is the people whos cames to Public health center to get treatment. Sample of case is 52 people and sample of control is 52 people. The variable in this research is Personal Protective equipments. The data were analyzed by univariate and bivariate analysis using Pearson correlation test and simple linier regression.The result of this research is that there is a significant correlation of using personal protective equipments with ARI in the dry season with (p value < 0,01). The preventive of action that can be done by the community is that if driving in the dry season, you should use PPE (Personal Protective equipments) like a mask, and if you are often active in the sun, you should use protective clothing such as hats, long sleeves, trousers and hats to avoid direct sun exposure.